2003
DOI: 10.1007/s10340-003-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the striped stem borer Chilo suppressalis (Walk.) (Lep., Pyralidae) larvae and rice plants in response to nitrogen fertilization

Abstract: Interactions between the striped stem borer Chilo suppressalis (Walk.) (Lep., Pyralidae) larvae and rice plants in response to nitrogen fertilization Abstract A screenhouse experiment was conducted to examine the damage and compensation in rice plants when injured by the striped stem borer, Chilo suppressalis (Walker), larvae at tillering stage, as well as larval survival and development of the insect at different nitrogen (N) fertilization levels. Potted plants were fertilized at late seedling stage at the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…Higher fertilizer use has often been associated with increased planthopper and stem borer fitness and with higher levels of damage to rice plants (Cheng, ; Preap et al., ; Jiang & Cheng, ; Lu et al., ). Stem borers and other lepidopterans also have higher survival, faster growth rates, and attain a greater biomass on plants with high nitrogen applications and/or with applications of inorganic fertilizers (Dhandapani et al., ; Gill et al., ; Gines et al., ; Jiang & Cheng, ; Huang et al., ). However, in a recent study using a range of hybrids and their respective inbred parental lines, Crisol et al.…”
Section: Does Hybrid Management Contribute To Damage From Insect Herbmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher fertilizer use has often been associated with increased planthopper and stem borer fitness and with higher levels of damage to rice plants (Cheng, ; Preap et al., ; Jiang & Cheng, ; Lu et al., ). Stem borers and other lepidopterans also have higher survival, faster growth rates, and attain a greater biomass on plants with high nitrogen applications and/or with applications of inorganic fertilizers (Dhandapani et al., ; Gill et al., ; Gines et al., ; Jiang & Cheng, ; Huang et al., ). However, in a recent study using a range of hybrids and their respective inbred parental lines, Crisol et al.…”
Section: Does Hybrid Management Contribute To Damage From Insect Herbmentioning
confidence: 99%
“…Higher fertilizer inputs associated with hybrid varieties could increase hybrid vulnerability to a range of insect herbivores (hypothesis B4) although it may also increase hybrid tolerance to herbivore damage (hypothesis B5). Higher fertilizer use has often been associated with increased planthopper and stem borer fitness and with higher levels of damage to rice plants (Cheng, 1971;Preap et al, 2001;Jiang & Cheng, 2003;Lu et al, 2004). Stem borers and other lepidopterans also have higher survival, faster growth rates, and attain a greater biomass on plants with high nitrogen applications and/or with applications of inorganic fertilizers (Dhandapani et al, 1990;Gill et al, 1993;Gines et al, 1994;Jiang & Cheng, 2003;Huang et al, 2010).…”
Section: Fertilizersmentioning
confidence: 99%
“…These correlations might have resulted from growth or/and physiological compensations in the injured plants. Compensation in rice plants due to stem borer attack has been well documented in earlier studies (Lu, 1987;Sun and Du, 1992;Rubia et al, 1996;Jiang and Cheng, 2003). They might also have resulted from preference of stem borers for infesting larger plants where higher injury levels consequently occurred, or from some other unmeasured plant attributes to which stem borers respond.…”
Section: Discussionmentioning
confidence: 65%
“…They also indicated that 33% dead hearts in 30-d-old plants did not have a signiÞcant effect on productive tillers or grain yield. Jiang and Cheng (2003) reported that rice plants infested with Asiatic rice borer, Chilo suppressalis (Walker) (Lepidoptera: Crambidae), produced approximately one more tiller than untreated control plants 2 wk after infestation. Studies also have shown that low insect infestation levels at early growth stages may increase plant yield in Þeld beans, Phaseolus vulgaris L. (Banks and Macaulay 1967); wheat (Triticum spp.…”
Section: Discussionmentioning
confidence: 99%